1989
DOI: 10.1002/1097-4679(198905)45:3<369::aid-jclp2270450304>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Factor analytic study of depressive disorders

Abstract: 369In summary, the findings of this investigation support the concurrent validity of many of the MMPI scales for DSM-I11 personality disorders. The failure of some MMPI scales to show adequate convergent validity is probably due to inappropriate criterion measures. Of course, the results of this study are based on a relatively small sample of psychiatric patients and need to be replicated on other populations that have higher representations of outpatients. Also, because patients were referred for psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Since the melancholic features of depression, such as diurnal variations in mood and insomnia (21), imply melatonin abnormalities and related circadian rhythm dysfunctions, the present results showing greater pineal atrophy in the nonmelancholic MDD subtype were unexpected. On the other hand, we demonstrated that the severity of loss of interest, one of the core factors of melancholic depression (32), correlated with the degree of pineal reduction. While some neuroimaging [e.g., hippocampal atrophy (33) and hypofrontality (34)] and neuroendocrine [e.g., abnormal dexamethasone suppression pattern (35)] findings appear to be associated with the pathophysiology of melancholia, there have been no definitive biological markers of different subtypes of depression (35).…”
Section: Discussionmentioning
confidence: 73%
“…Since the melancholic features of depression, such as diurnal variations in mood and insomnia (21), imply melatonin abnormalities and related circadian rhythm dysfunctions, the present results showing greater pineal atrophy in the nonmelancholic MDD subtype were unexpected. On the other hand, we demonstrated that the severity of loss of interest, one of the core factors of melancholic depression (32), correlated with the degree of pineal reduction. While some neuroimaging [e.g., hippocampal atrophy (33) and hypofrontality (34)] and neuroendocrine [e.g., abnormal dexamethasone suppression pattern (35)] findings appear to be associated with the pathophysiology of melancholia, there have been no definitive biological markers of different subtypes of depression (35).…”
Section: Discussionmentioning
confidence: 73%
“…The search strategy identified 154 papers (Robins et al 1959 ;Dorpat & Ripley, 1960 ;Litman et al 1963 ;Seager & Flood, 1965 ;Faberow & Mc-Evoy, 1966 ;Rudestam, 1971Rudestam, , 1979Shaffer et al 1972 ;Barraclough et al 1974 ;Neill et al 1974;Barraclough & Pallis, 1975;Heiman, 1975;Sanborn & Sanborn, 1976;Diller, 1979;Murphy et al 1979Murphy et al , 1992Chynoweth et al 1980 ;Weston, 1980 ;Heilig et al 1982;Roy, 1982Roy, , 1983Roy, , 1992Litman, 1984Litman, , 1989Litman, , 1996Shafii et al 1985Shafii et al , 1988Allebeck et al 1986 ;Fowler et al 1986;Rich et al 1986Rich et al , 1988Rich et al , 1990Berglund et al 1987 ;Biro, 1987 ;Brent et al 1987Brent et al , 1988Brent et al a, b, 1994Brent et al , 1999Arato et al 1988;Shaffer, 1988 ;Andersson-Segesten, 1989;Brent, 1989…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-five papers were judged eligible for inclusion. Fifty-three were case series reports (Robins et al 1959 ;Dorpat & Ripley, 1960 ;Litman et al 1963 ;Rudestam, 1971;Barraclough et al 1974 ;Murphy et al 1979;Chynoweth et al 1980 ;Fowler et al 1986 ;Rich et al 1986Rich et al , 1988Rich et al , 1990Biro, 1987 ;Arato et al 1988 ;Rao et al 1989 ;Runeson, 1989 ;Å sga˚rd, 1990 ;Conwell et al 1990Conwell et al , 1991Conwell et al , 1996Conwell et al , 1998Martunnen et al 1991Martunnen et al , 1993aMartunnen et al , 1994Martunnen et al a, b, 1995Martunnen et al , 1997Heikkinen et al 1992Heikkinen et al , 1994Heikkinen et al , 1995Horton-Deutsch et al 1992 ;Apter et al 1993 ;Duberstein et al 1993;Henriksson et al 1993Henriksson et al , 1995aHenriksson et al , 1996Isacsson et al 1994 ;Isometsa¨et al 1994aIsometsa¨et al , b, c, d, 1995aIsometsa¨et al , b, 1996Isometsa¨et al a, b, 1997Kelly & Mann, 1996;Sorri et al 1996 ;Foster et al 1997;…”
Section: Resultsmentioning
confidence: 99%